Proceedings of Rapid Excavation and Tunelling - Rapid Excavation and Tunneling Conference, 3rd., Las Vegas, Nevada, June 14-17, 1976; Robbins, Richard J; Coulon, Robert J.; American Institute of Mining, Metallurgical and Petroleum Engineers (New York : American Institute of Mining, Metallurgical and Petroleum Engineers, 1976)
08